Analysis of Entrepreneurial Activities for Promoting Organic Products in Karnali Province - Rokaya, Ammar Bahadur; Pandey, Akhilesh Chandra (KMC Journal, 2023)
Organic products not only provide numerous health benefits but also contribute to environmental sustainability. The entrepreneurial skills needed for the promotion of organic products in the Karnali province of Nepal can contribute significantly to the regional economy. But it requires a comprehensive policy framework to support and encourage the growth of this sector. The purpose of this study is to explore the current status of entrepreneurial activities to produce and promote organic products in the Karnali province and identify the challenges faced by entrepreneurs in this sector. The study is based on qualitative methods, including in-depth interviews with leading entrepreneurs, government authorities, and experts by using quota and convenience sampling techniques, and a review of relevant literature. This study finds the effective strategies for promoting entrepreneurship in the organic products sector in the Karnali province of Nepal. By analyzing the current state of organic agriculture and entrepreneurship development in the region, the study provides the recommendations for policymakers to support the growth of entrepreneurs in this sector. The findings suggest for the implications for the local community and the environment, as promoting organic agriculture with positive effects. Overall, this study seeks to contribute to the development of policies that promote entrepreneurship and sustainable development in the Karnali province.